2020
DOI: 10.1080/17461391.2020.1776401
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association research in football: A systematic review

Abstract: Genetic variation is responsible for a large amount of the inter-individual performance disparities seen in sport. As such, in the last ten years genetic association studies have become more common; with one of the most frequently researched sports being football. However, the progress and methodological rigor of genetic association research in football is yet to be evaluated. Therefore, the aim of this paper was to identify and evaluate all genetic association studies involving football players and outline wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…As a result, studies require large homogenous sample sizes in order to have sufficient statistical power and demonstrate significant associations and replications 45,47 . However, studies within football genomics have notoriously small sample sizes and many are heterogenic multi-sport studies; mainly due to the unique population and limited access available 48 . Therefore, to overcome the limitation of sample sizes and heterogeneity, a meta-analysis can be used to pool the results of single homogenous studies together 47 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, studies require large homogenous sample sizes in order to have sufficient statistical power and demonstrate significant associations and replications 45,47 . However, studies within football genomics have notoriously small sample sizes and many are heterogenic multi-sport studies; mainly due to the unique population and limited access available 48 . Therefore, to overcome the limitation of sample sizes and heterogeneity, a meta-analysis can be used to pool the results of single homogenous studies together 47 .…”
Section: Introductionmentioning
confidence: 99%
“…First, this may represent an increased interest in genetic testing in sport, corresponding with the increase in sport genomic research in recent years [30]. More specifically in football, McAuley and colleagues [17] showed that 55% of genetic association studies involving football players have been published within the last 4 years. Second, this increased proportion could also illustrate a more accurate representation of the true, and larger, prevalence of genetic testing within professional football.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the paucity of genetic research on psychological traits in football. Indeed, a recent systematic review showcased that out of 80 genetic association studies involving football players, only three studies investigated psychological traits compared to 20 on physiological traits [17]. As such, in football, there is currently a limited psychogenetic evidence base available to key stakeholders to form their opinions on genetic associations with psychological traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations may seem obvious, but we would note that a recent scoping review of talent research found that~15% of studies did not report gender and 22% did not report nationality (Baker et al, 2020). Indeed, inadequate reporting of participant characteristics is a common finding throughout research syntheses in sport (McAuley et al, 2020a). Overall, this greater transparency will allow readers to determine their personal classifications for samples more effectively, and thus facilitate improved research synthesis and practical interpretations.…”
Section: A Call For Transparencymentioning
confidence: 97%